2022
DOI: 10.1111/bjet.13233
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating AI and learning analytics to build trustworthy peer assessment systems

Abstract: Peer assessment has been recognised as a sustainable and scalable assessment method that promotes higher‐order learning and provides students with fast and detailed feedback on their work. Despite these benefits, some common concerns and criticisms are associated with the use of peer assessments (eg, scarcity of high‐quality feedback from peer student‐assessors and lack of accuracy in assigning a grade to the assessee) that raise questions about their trustworthiness. Consequently, many instructors and educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…Although the considerable amount of false positives and a few borderline false negatives in Fig. 5 demonstrate an evident necessity for instructors' support during the moderation process, which is aligned with the findings of previous studies [10], [97], [98], the use of advanced consensus approaches can significantly reduce the instructors' load in the quality assessment of SGC at scale.…”
Section: Discussionsupporting
confidence: 86%
“…Although the considerable amount of false positives and a few borderline false negatives in Fig. 5 demonstrate an evident necessity for instructors' support during the moderation process, which is aligned with the findings of previous studies [10], [97], [98], the use of advanced consensus approaches can significantly reduce the instructors' load in the quality assessment of SGC at scale.…”
Section: Discussionsupporting
confidence: 86%
“…Particularly, the integration of AI and LA has potential to provide both quantitative performance generated by AI model and qualitative feedback from the instructor’s or researcher’s perspectives, which can further improve student learning process and performance. For example, Darvishi et al ( 2022 ) incorporated AI and LA to build a trustworthy peer assessment system and this research showed that this AI-assisted and analytical approaches integrated AI model to improve the accuracy of the assigned task for the instructors. Students, supported with the integrated AI and LA techniques, successfully wrote lengthier and more helpful feedback comments to peers, which improved their learning effects and final performances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Particularly, AI can automatically capture and analyze the learning process and the learner's psychological states, and LA can provide relevant feedback and suggestions from the educators or practitioners concerning the cognitive process, social interaction, and affectional or metacognitive states (Starcic, 2019). More importantly, relevant literature indicates that the integrated AI and LA techniques have potential to eventually improve students' learning performances (e.g., Chango et al, 2021;Darvishi et al, 2022).…”
Section: Effect Of Ai Performance Prediction Models: From the Educati...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in certain cases, utility tends to increase when LA models are built without protected attributes, such as gender or socio‐economic status. Finally, Darvishi et al (2022) present a systematic approach of using LA and AI‐based methods in peer assessment processes, aiming at increasing trustworthiness, effectiveness, and efficiency, which in turn might enhance adoption of such assessment processes. Darvishi and colleagues show results on a large dataset using a concrete adaptive system with peer assessment functionalities over several courses.…”
mentioning
confidence: 99%